Understanding the impact of introducing Lambda expressions in Java Programs - Lucas, Walter (2020)
Background: The Java programming language version eight introduced several features that encourage the func tional style of programming, including the support for lambda expressions and the Stream API. Currently, there is a common wisdom that refactoring legacy code to introduce lambda expressions, besides other potential benefits, simplifies the code and improves program comprehension. Aims: The purpose of this work is to investigate this belief, conducting an indepth study to evaluate the effect of introducing lambda expressions on program comprehension. Method: We conducted this research using a mixedmethod approach. For the quantitative method, we quantitatively analyzed 158 pairs of code snippets extracted directly either from GitHub or from recommendations from three tools (RJTL, NetBeans, and IntelliJ). We also surveyed practitioners to collect their perceptions about the benefits on program comprehension when introducing lambda expressions. We asked practitioners to evaluate and rate sets of pairs of code snippets. Results: We found contradictory results in our research. Based on the quantitative assessment, we could not find evidence that the introduction of lambda expressions improves software readability— one of the components of program comprehension. Our results suggest that the transformations recommended by the aforementioned tools decrease program comprehension when assessed by two stateoftheart models to estimate readability. Differently, our findings of the qualitative assessment suggest that the introduction of lambda expression improves program comprehension in three scenarios when: we convert anonymous inner classes to a lambda expression, use structural loops with inner conditional to an anyMatch operator, and apply structural loops to filter operator combined with a collect method. Implications: We argue in this paper that one can improve program comprehension when he/she applies particular transformations to introduce lambda expressions (e.g., replacing anonymous inner classes with lambda expressions). Also, the opinion of the participants highlights which kind of transformation for introducing lambda might be advantageous. This might support the implementation of effective tools for automatic program transformations.